2009
DOI: 10.1161/circresaha.109.197517
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145, a Novel Smooth Muscle Cell Phenotypic Marker and Modulator, Controls Vascular Neointimal Lesion Formation

Abstract: Abstract-Phenotypic modulation of vascular smooth muscle cells (VSMCs) plays a critical role in the pathogenesis of a variety of proliferative vascular diseases. Recently, we have found that microRNA (miRNA) miR-145 is the most abundant miRNA in normal vascular walls and in freshly isolated VSMCs; however, the role of miR-145 in VSMC phenotypic modulation and vascular diseases is currently unknown. Here we find that miR-145 is selectively expressed in VSMCs of the vascular wall and its expression is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

35
655
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 607 publications
(692 citation statements)
references
References 19 publications
35
655
1
1
Order By: Relevance
“…Indeed, TGF-␤1-induced miR145 was impaired when endogenous MYOCD was knocked down. Interestingly, recent studies have postulated that miR145 may augment MYOCD mRNA to establish a feedforward mechanism for SMC differentiation (34,35). We attempted to examine if such a mechanism was operative in HCASM but were unable to observe consistent activation of MYOCD by miR145.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TGF-␤1-induced miR145 was impaired when endogenous MYOCD was knocked down. Interestingly, recent studies have postulated that miR145 may augment MYOCD mRNA to establish a feedforward mechanism for SMC differentiation (34,35). We attempted to examine if such a mechanism was operative in HCASM but were unable to observe consistent activation of MYOCD by miR145.…”
Section: Discussionmentioning
confidence: 99%
“…The human miR-143/miR-145 (miR-143/145) cluster on chromosome 5q33 is regulated by a common promoter (20). miR-143/ 145 are transcriptional targets of SRF via the CArG box sequence, and act to promote VSMC differentiation through translational repression of proliferation associated proteins KLF5 (21) and member of the ETS oncogene family (Elk1) (22). Targeted deletion of the mouse miR-143/145 cluster showed it to be dispensable for VSMC differentiation, although it is required for the maintenance of VSMC cytoskeletal architec-* This work was supported, in whole or in part, by National Institutes of Health Grants R01 HL070865 (to L. L.) and P20RR15555 from the National Center for Research Resources (to R. E. Friesel and L. L.).…”
mentioning
confidence: 99%
“…18 Therefore, at least two marker proteins that are associated with the contractile phenotype are used to distinguish a contractile SM cell from a proliferative SM cell in many current documents. 19,21 In this study, we tested the expressions of five contractility-associated markers, including SMA, calponin, SMMHC, smoothelin and myocardin, and found that all of them were downregulated at the mRNA level in cavernous tissues of diabetic ED rats. Among these marker proteins, SMA is an excellent SM cell contractile marker, which is the first known protein expressed during differentiation of SM cells, 22 and is most widely used.…”
Section: Discussionmentioning
confidence: 99%
“…18 A variety of SM cell marker proteins, such as SMA, calponin, SMMHC, smoothelin, myocardin, h-caldesmon, telokin, metavinculin and desmin, were commonly used to define the SM cell phenotype. 8,19 Many of these proteins are involved in SM cell contraction, either as a structural component of the contractile apparatus or as a regulator of contraction, and they are called contractility- associated markers. In contrast, as many of the other proteins, such as smemb and cell retinol binding protein-1, 20 are quickly and markedly upregulated in proliferating SM cells, they are used as proliferative SM cell markers.…”
Section: Discussionmentioning
confidence: 99%